1977
DOI: 10.1071/ar9770737
|View full text |Cite
|
Sign up to set email alerts
|

The description and analysis of wool growth

Abstract: Analyses of experimental estimates of the wool growth rate as a function of intake have previously been based on time-independent equations and linear regression with ordinary least squares. Some of these results are reanalysed with the assumption that the sheep is a dynamic system; hence a timedependent description of wool growth is proposed. A recursive least squares technique has been used, and the results demonstrate that there is a 34 week lag between intake and wool growth. Time-independent descriptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…For example, results for SS are often confounded by pre-existing wool growth under different and usually undocumented conditions. Many investigations also fail to take into account the lag phase effects from previous management on wool attributes which take about 21 days to be overcome (Nagorcka, 1977).…”
Section: Experimental Approachesmentioning
confidence: 99%
“…For example, results for SS are often confounded by pre-existing wool growth under different and usually undocumented conditions. Many investigations also fail to take into account the lag phase effects from previous management on wool attributes which take about 21 days to be overcome (Nagorcka, 1977).…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Also there is an apparent 3! week lag between feed intake and wool growth (Nagorcka 1977). The process of regrowth involved the exfoliation of fibre remnants and epithelial debris from the upper parts of the follicles and restoration of normal follicle structure.…”
Section: Discussionmentioning
confidence: 99%
“…Sharkey et al (1962) and Sharkey and Hedding (1964) showed that liveweight relationships with wool growth were influenced by liveweight or liveweight change in the proceeding time periods due to delays in wool growth responses to changing nutrition. Nagorcka (1977), in an analysis of experimental estimates of wool growth, indicated a 3.5-week lag between changes in feed intake and wool growth. This lag appeared to be of similar order of magnitude to those reported for grazing experiments (Stewart et al 1961;Purser 1980;Revell et al 1994).…”
Section: Discussionmentioning
confidence: 98%